The Effect of Profitability, Liquidity, and Dividend Policy on Firm Value With Capital Structure as an Intervening Variable in Companies in the Consumer Cyclicals Sector on the Indonesian Stock Exchange - Adrianti, Aprila; Suryadi, Edy (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the influence of profitability, liquidity, and dividend policy on firm value with capital structure as an intervening variable in consumer cyclicals companies listed on the Indonesia Stock Exchange during the period 2021-2023. This study uses secondary data obtained from official websites such as www.idx.co.id and www.bi.go.id. The sample consists of 114 companies, selected using purposive sampling. Data analysis techniques include normality tests, multicollinearity tests, autocorrelation tests, heteroskedasticity tests, linearity tests, and path analysis to examine the relationships between variables. The results of the study indicate that in the first simultaneous test (F-test), there is no significant influence between profitability, liquidity, dividend policy, and capital structure on firm value. However, in the second regression, which included capital structure as an intervening variable, it was found that profitability, liquidity, and dividend policy significantly influenced firm value. The t-test results showed that in the first regression, profitability, liquidity, dividend policy, and capital structure did not significantly influence firm value, as the t-statistic values were smaller than the t-table values and the significance values were greater than 0.05. Meanwhile, in the second regression, the variables profitability, liquidity, and dividend policy through capital structure have a significant influence on firm value, with t-statistics greater than the t-table value and significance values less than 0.05. Future research may consider additional variables such as risk management and external factors to deepen understanding of the factors influencing company value in other sectors.